Reflective Written Pieces: Inquiry into the Practices of Pre-service Literacy Teachers - Janet McIntosh (Networks: An Online Journal for Teacher Research, 2017)
The purpose of this action research project was to explore whether a reflective writing strategy, developed and used with pre-service teachers in a literacy methods course, assisted them with integrating theory and practice. The teacher educator analyzed the written reflective pieces and determined common categories. Study findings revealed some themes: meeting student needs, classroom strategies, field link experiences, personal student experiences, and growth statements. Pre-service teachers explored what their current knowledge was and how it had changed through the time spent reading and writing in the course; imbedded within the reflection pieces were references to practicum experiences with students in classrooms. Through the act of writing their thoughts down, they indicated changes in their individual views about how to approach literacy teaching. Findings reveal that the reflective writing strategy served as an effective starting point for pre-service literacy teachers’ emerging development.